2021
DOI: 10.3390/ijms222011156
|View full text |Cite
|
Sign up to set email alerts
|

Paracetamol (Acetaminophen) and the Developing Brain

Abstract: Paracetamol is commonly used to treat fever and pain in pregnant women, but there are growing concerns that this may cause attention deficit hyperactivity disorder and autism spectrum disorder in the offspring. A growing number of epidemiological studies suggests that relative risks for these disorders increase by an average of about 25% following intrauterine paracetamol exposure. The data analyzed point to a dose–effect relationship but cannot fully account for unmeasured confounders, notably indication and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 91 publications
0
8
0
Order By: Relevance
“…Since NAPQI mainly tends to bind to structures containing the -SH group, NAPQI rapidly binds especially to cellular GSH while forming and is detoxified in this way. However, after excessive doses of APAP use, an excessive amount of NAPQI occurs in the cell, and when the decreased GSH levels cannot meet the increased amount of NAPQI, NAPQI, a reactive metabolite of APAP, binds to other -SH-containing cellular proteins, causing suppression of mitochondrial respiration and development of cellular damage [27,28,29].…”
Section: Resultsmentioning
confidence: 99%
“…Since NAPQI mainly tends to bind to structures containing the -SH group, NAPQI rapidly binds especially to cellular GSH while forming and is detoxified in this way. However, after excessive doses of APAP use, an excessive amount of NAPQI occurs in the cell, and when the decreased GSH levels cannot meet the increased amount of NAPQI, NAPQI, a reactive metabolite of APAP, binds to other -SH-containing cellular proteins, causing suppression of mitochondrial respiration and development of cellular damage [27,28,29].…”
Section: Resultsmentioning
confidence: 99%
“…As APAP can pass through the blood-brain barrier, it can act both centrally and peripherally through different molecular regulatory mechanisms. For example, one of the mechanisms of APAP action is thought to relieve pain is through competitive suppression of the peroxidase moiety of prostaglandin H2 synthase and regulation of cannabinoid receptor signaling pathway ( Bührer et al, 2021 ). Additionally, APAP has also been found to inhibit serotonergic mechanisms for relieving pain in clinical studies ( Pickering et al, 2008 ).…”
Section: Apap-exerted Neuroendocrine Disrupting Actionsmentioning
confidence: 99%
“…This summary statement called for increased awareness of the potential role of APAP in this phenomenon, but it was criticized heavily by the American College of Obstetricians and Gynecologists (ACOG). In its response [ 15 ], the ACOG concluded that available studies “show no clear evidence that proves a direct relationship between the prudent use of APAP during any trimester and fetal developmental issues.” The ACOG further concluded that “physicians should not change clinical practice until definitive prospective research is done.” Considering the ACOG response, it is important to note that evidence of APAP inducing neurodevelopmental problems during the prenatal period is concerning but limited [ 2 , 16 , 17 ]. As shown in Table 1 , only one of 20 lines of evidence was related only to the prenatal period.…”
Section: Introductionmentioning
confidence: 99%